Ukrainian religious migration as a challenge to ecumenism in Poland - Dobroier, Oleksandr (Verbum vitae, 2025)
This article analyzes how military migration from Ukraine has changed the religious field in Poland. The author examines the impact of a large number of Ukrainian Christians of different denominations on the transformation of interchurch relations in Polish churches and their rethinking of confessional identity and pastoral approaches. The article examines the church environment of the three main denominations: Catholicism, Orthodoxy, and Protestantism. The research method used includes eleven semi-structured interviews with clergy and theologians of different denominations, as well as discourse analysis of church documents and media. As a result, new modes of ecumenical interaction have been identified: from institutional dialogue to practical concelebration and humanitarian cooperation. Military migration has become a catalyst for changes in Polish ecumenism from formal diplomacy to solidarity action. This experience demonstrates that in times of war, ecumenism ceases to be only a theological concept and becomes a tool for responding to social challenges.